Patches
Patent Information
- Application Number
- CN201780080620.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Priority Date
- 2016-12-28
- Filing Date
- 2017-12-26
- Publication Date
- 2026-10-13
- Estimated Expiration
- 2037-12-26
AI Technical Summary
[0014]根据本发明的贴剂,通过使用具有高透湿度的支持体层,充分的附着性长时间持续。因此,即使长时间(例如24小时)应用,贴剂也不易剥落。其结果,在药物为具有镇痛且消炎作用的药物,例如酮洛芬、双氯芬酸钠或吲哚美辛时,将贴剂24小时贴附于患者的皮肤时,可更可靠地获得充分的累积皮肤透过量。另外,可更可靠地实现药物的最大血浆中浓度Cmax。因此,根据本发明的贴剂,可实现更有效的药物治疗。
Smart Images

Figure BDA0002107328960000091 
Figure BDA0002107328960000101 
Figure BDA0002107328960000111
Abstract
Description
Technical Field
[0001] This invention relates to a patch. Background Technology
[0002] Dimethyl sulfoxide (DMSO) is used to dissolve drugs in formulations. For example, patent document 1 discloses a diclofenac sodium patch that uses DMSO as a solvent.
[0003] Existing technical documents
[0004] Patent documents
[0005] Patent Document 1: International Publication No. 2013 / 191128 Summary of the Invention
[0006] The problem that the invention aims to solve
[0007] Typically, the adhesion of patches gradually decreases over time. The inventors have discovered that when DMSO is incorporated into the adhesive layer of a patch, the composition that provides the adhesiveness of the patch undergoes plasticization, leading to a decrease in the adhesiveness of the adhesive layer. Furthermore, the inventors have found that when DMSO-containing patches are applied for extended periods (e.g., 24 hours), sufficient adhesion may not be maintained until the end, causing the patch to peel off before the treatment is complete.
[0008] Methods for solving problems
[0009] The inventors discovered that by combining an adhesive layer containing DMSO with a support having specific moisture permeability, the adhesion of the patch after prolonged application is greatly improved, thus completing the present invention.
[0010] The patch of the present invention comprises a support layer and an adhesive layer laminated on the support layer, wherein the moisture permeability of the support layer is 400 g / m². 2 • For more than 24 hours, the adhesive layer contains drugs, DMSO, and adhesives. The moisture permeability of the support layer can be 750 g / m². 2 • 24 hours or more, or 2000g / m 2 • More than 24 hours.
[0011] The adhesive layer may contain at least one adhesive selected from rubber-based adhesives, acrylic adhesives and silicone adhesives, or it may contain a styrene-isoprene-styrene block copolymer.
[0012] The drug can be one or more drugs selected from ketoprofen, diclofenac sodium, and indomethacin. Additionally, the adhesive layer may contain organic acids.
[0013] Invention Effects
[0014] The patch according to the invention maintains sufficient adhesion for a long time by using a support layer with high moisture permeability. Therefore, the patch is less prone to peeling even with prolonged application (e.g., 24 hours). As a result, when the drug is analgesic and anti-inflammatory, such as ketoprofen, diclofenac sodium, or indomethacin, sufficient cumulative skin penetration can be reliably achieved when the patch is applied to the patient's skin for 24 hours. Furthermore, the maximum plasma concentration C of the drug can be achieved more reliably. max Therefore, the patch according to the present invention enables more effective drug treatment. Attached Figure Description
[0015] [ Figure 1 [This is a graph (Example 1) showing the relationship between the moisture permeability of the support layer and the rate of decrease of the mass % concentration of DMSO relative to the total mass of the adhesive layer (hereinafter referred to as "DMSO concentration").]
[0016] [ Figure 2 [Figure 1] is a graph showing the relationship between the moisture permeability of the support layer and the half-life of the DMSO concentration (mass % concentration) relative to the total mass of the adhesive layer. Detailed Implementation
[0017] The patch of the present invention comprises a support layer and an adhesive layer laminated on the support layer. The adhesive layer is typically laminated on one side of the support layer, and, if necessary, a peelable film is laminated on the other side of the adhesive layer.
[0018] First, let's describe the adhesive layer. The adhesive layer is pressed onto the skin during patch application and contains at least the drug, DMSO, and adhesive.
[0019] The drug is a component soluble in DMSO. The drug can be analgesic and anti-inflammatory drugs such as loxoprofen, biphenylacetic acid, flurbiprofen, indomethacin, ketoprofen, and diclofenac sodium; or analgesics or anesthetics such as buprenorphine, fentanyl, and butorphanol; or other drugs such as clonidine, estradiol, tuloterol, and oxybutynin. The drug content relative to the total mass of the adhesive layer is, for example, 1% to 20% by mass or 2% to 10% by mass.
[0020] DMSO dissolves the drug and increases its skin permeability; however, it also reduces the adhesiveness of the adhesive layer. From the viewpoint of achieving a balance, the DMSO content relative to the total mass of the adhesive layer is preferably 1% to 20% by mass, more preferably 1% to 15% by mass, even more preferably 2% to 10% by mass, and particularly preferably 3% to 10% by mass.
[0021] The ratio of the drug to DMSO varies depending on the drug. For example, when diclofenac sodium is contained as the drug, in the adhesive layer of the patch before application, from the viewpoint of improving the skin permeability of diclofenac sodium and preventing the crystallization of diclofenac sodium, the mass ratio of the diclofenac sodium to DMSO contained is preferably 1:0.3 to 1:4, more preferably 1:0.4 to 1:3, further preferably 1:0.6 to 1:3, and particularly preferably 1:0.72 to 1:3.
[0022] The adhesive may contain at least one adhesive selected from rubber-based adhesives, acrylic adhesives, and silicone adhesives. Rubber-based adhesives include, for example, polyisoprene, polyisobutylene (PIB), polybutadiene, styrene-butadiene-styrene block copolymers, styrene-isoprene-styrene (SIS) block copolymers, styrene-butadiene rubber, styrene-isoprene rubber, or combinations thereof. From the viewpoint of improving drug permeability and further enhancing the adhesion of the patch, SIS block copolymers, PIB, or combinations thereof are preferred, and a mixture of SIS block copolymers and PIB is more preferred. Acrylic adhesives are, for example, adhesives polymerized or copolymerized from at least one of (meth)acrylic acid monomers such as (meth)acrylic acid, 2-ethylhexyl (meth)acrylic acid, methyl (meth)acrylic acid, butyl (meth)acrylic acid, and hydroxyethyl (meth)acrylic acid. Silicone adhesives are, for example, silicone rubbers such as polydimethylsiloxane, polymethylvinylsiloxane, and polymethylphenylsiloxane as the main component.
[0023] When using rubber-based adhesives, from the viewpoint of adhesiveness, the adhesive content relative to the total mass of the adhesive layer can be 10% to 70% by mass, 10% to 40% by mass, 15% to 50% by mass, 15% to 35% by mass, or 30% to 40% by mass. When using acrylic or silicone-based adhesives, the adhesive content relative to the total mass of the adhesive layer can be 50% to 90% by mass.
[0024] To promote transdermal drug absorption or prevent drug crystallization over time, the adhesive layer may also contain organic acids. Examples of organic acids include: aliphatic monocarboxylic acids (formic acid, acetic acid, propionic acid, butyric acid, isobutyric acid, valeric acid, hexanoic acid, heptanoic acid, octanoic acid, nonanoic acid, decanoic acid, lauric acid, oleic acid, linoleic acid, linolenic acid, isostearic acid, sorbic acid, pyruvic acid, etc.), aliphatic dicarboxylic acids (oxalic acid, malonic acid, succinic acid, glutaric acid, adipic acid, sebacic acid, maleic acid, fumaric acid, oxaloacetic acid, etc.), and aliphatic tricarboxylic acids (aconitic acid, propanetricarboxylic acid). Aliphatic carboxylic acids (e.g., glycolic acid, lactic acid, hydroxymalonic acid, glyceric acid, hydroxybutyric acid, malic acid, tartaric acid, citric acid, isocitric acid, glycolic acid, gluconic acid, glucuronic acid, ascorbic acid, isoascorbic acid, etc.); aromatic carboxylic acids (benzoic acid, gallic acid, salicylic acid, acetylsalicylic acid, phthalic acid, etc.); other organic acids (methanesulfonic acid, benzenesulfonic acid, etc.); or their salts (e.g., alkali metal salts such as sodium salts). Among these organic acids, when the drug is diclofenac sodium, citric acid, oleic acid, methanesulfonic acid, or their alkali metal salts are particularly preferred from the viewpoint of promoting the transdermal absorption of diclofenac sodium and preventing the crystallization of diclofenac sodium over time. By containing these organic acids, a sufficient cumulative skin penetration of the drug can be reliably obtained. These organic acids can be used alone or in combination of two or more. From the viewpoint of improving the skin permeability of the drug and preventing the crystallization of the drug over time, the content of organic acid relative to the total mass of the binder layer can be 0.01% to 20% by mass, 0.1% to 15% by mass, or 0.2% to 13% by mass.
[0025] The adhesive layer may also contain tackifiers, plasticizers, or other additives. Tackifiers are, for example, alicyclic saturated hydrocarbon resins, hydrogenated rosin esters, terpene resins, or combinations thereof. The tackifier content relative to the total mass of the adhesive layer is, for example, 5% to 60% by mass, 10% to 50% by mass, 25% to 45% by mass, or 30% to 35% by mass. Plasticizers are, for example, liquid paraffin or liquid polybutene. The plasticizer content relative to the total mass of the adhesive layer is, for example, 7% to 70% by mass, 10% to 60% by mass, or 11% to 25% by mass.
[0026] The adhesive layer can be a single layer composed of one type of material, or a multilayer composed of multiple layers of different materials stacked together. From the viewpoint of properly adhering the patch to the skin, the overall thickness of the adhesive layer is preferably 10 μm to 1000 μm, more preferably 30 μm to 300 μm.
[0027] The probe tack value of the adhesive layer is preferably 30 gF or higher, more preferably 40 gF or higher. For example, the probe tack value of the adhesive layer can be 43 gF or higher, 44 gF or higher, 53 gF or higher, 61 gF or higher, 68 gF or higher, or 71 gF or higher. A higher probe tack value results in better adhesion of the patch. From the viewpoint of reducing skin irritation, the probe tack value can be 2000 gF or lower, 1500 gF or lower, or 1000 gF or lower. In this specification, the probe tack value of the adhesive layer is determined according to the probe tack test method of ASTM D2979.
[0028] Next, the support layer will be described. The support layer holds the adhesive layer together. The moisture permeability of the support layer is 400 g / m². 2 • Over 24 hours. When using this highly moisture-permeable support layer, DMSO gradually evaporates from the patch applied to the skin, thus improving the patch's adhesion and preventing it from peeling off even after prolonged use. While moisture permeability is typically an indicator of water permeability, the inventors have discovered that supports with higher moisture permeability also exhibit higher DMSO permeability (volatility). For example, the moisture permeability of the support layer can be 422 g / m³. 2 • More than 24 hours, 750g / m 2 • More than 24 hours, 2000g / m 2 • More than 24 hours, 2077g / m 2 • More than 24 hours, 4000g / m 2 • More than 24 hours, 5500g / m 2 • More than 24 hours, 5667g / m 2 • More than 24 hours, or 8408g / m 2 • More than 24 hours. The upper limit for moisture permeability is 20000g / m². 2 • 24 hours. When the moisture permeability of the support layer is within this range, DMSO evaporates more easily from the adhesive layer, thus improving the adhesion of the patch more effectively.
[0029] To clarify, the moisture permeability of the support layer of this invention refers to the moisture permeability at 40°C as defined in the JIS Z0208:1976 standard (Test method for moisture permeability of moisture-proof packaging materials (cup method)).
[0030] The support layer is preferably a single layer or laminate of fibers made into a fabric-like (woven, non-woven, or braided) material, or a single layer or laminate of a non-porous or porous membrane (sheet). The material of the support layer is preferably selected from one or more of the following: polyester (polyethylene terephthalate (PET), polyethylene isophthalate, polypropylene terephthalate, polybutylene terephthalate, or polyethylene naphthalate, etc.), polyolefin (polymers or copolymers of ethylene monomers such as ethylene, propylene, vinyl acetate, or acrylonitrile), polyamide (nylon or silk, etc.), polyurethane (PU), or cellulose (kapok or hemp, etc.). A rubber composition can be coated onto the fabric (woven, non-woven, or braided). The rubber composition contains a rubber-based adhesive. Rubber-based adhesives include, for example, polyisoprene, PIB, polybutadiene, styrene-butadiene-styrene block copolymers, SIS block copolymers, styrene-butadiene rubber, styrene-isoprene rubber, or combinations thereof. The rubber composition may also contain tackifiers. Tackifiers include, for example, alicyclic saturated hydrocarbon resins, hydrogenated rosin esters, terpene resins, or combinations thereof. Additionally, the rubber composition may contain additives such as plasticizers and fillers. The thickness of the support layer is, for example, 0.1 mm to 2 mm. The weight per unit area of the support layer is, for example, 30 g / m². 2 ~200g / m 2 In this specification, the thickness and weight per unit area of the support layer are measured according to JIS L 1906:2000.
[0031] When the support layer is fabric-like, the 50% modulus (JIS L 1018:1999) in either the longitudinal (material travel direction) or transverse (material width direction) direction of the support layer is preferably 1 N / 50 mm to 12 N / 50 mm. When the 50% modulus is below 12 N / 50 mm, the patch experiences less stress due to skin stretching, thus resulting in good adhesion to the skin.
[0032] When the support layer is a membrane, the material preferably has high moisture permeability (high DMSO permeability) like polyurethane. Membranes containing polyurethane have excellent elasticity, and are therefore preferred from the viewpoint of improving the patch's adhesion to the skin and its ability to follow stretch.
[0033] The support layer is preferably, for example, a nonwoven fabric or film containing polyurethane, a woven fabric containing polyethylene terephthalate, a polyester fabric coated with a rubber composition, or a combination thereof. More specifically, the support layer is preferably a laminate of a polyurethane-containing film and a nonwoven fabric containing polyurethane fibers, a nonwoven fabric containing PET fibers, or a polyester fabric coated with a rubber composition.
[0034] From the viewpoint of preventing drug precipitation in unused patches, the DMSO concentration in the patch immediately before application, for example relative to the total mass of the adhesive layer, can be 1% to 20% by mass, 2% to 12% by mass, 2% to 10% by mass, or 2% to 8% by mass. Furthermore, the DMSO concentration in the patch 24 hours after application is preferably 0.1% to 4% by mass, more preferably 0.1% to 1.5% by mass. As the support layer, a support layer that allows for such a decrease in DMSO concentration is preferred. More specifically, when the DMSO concentration in the patch immediately before application is 2% to 8% by mass, a support layer that allows the DMSO concentration to decrease at a rate of 0.08% by mass / hour to 0.16% by mass / hour (i.e., a decrease of 1.92% to 3.84% by mass every 24 hours) is preferred. From another perspective, when the DMSO concentration in the patch immediately before application is 2% to 8% by mass, a support layer with a DMSO half-life of 5 to 24 hours is preferred. A support layer that meets these conditions tends to maintain sufficient adhesion even 24 hours after application. To clarify, the rate of decrease in DMSO concentration and the half-life of the patch described above were calculated using the following method: the patch was prepared with the support layer facing upwards at 30°C and 65% RH, and the change in DMSO concentration was measured by gas chromatography (GC).
[0035] The patch can be manufactured, for example, by the following method, but is not limited to this, and well-known methods can be used. First, the components constituting the adhesive layer are mixed in a specific ratio to obtain a homogeneous solution. Next, the solution is coated to a specific thickness on a peelable film (release film, release liner) to form an adhesive layer. Then, the support layer is pressed onto the adhesive layer in such a way that the release liner and the support layer are sandwiched between the adhesive layer. Finally, the patch is obtained by cutting it into the desired shape. In this case, the release liner is removed when the patch is applied.
[0036] Example
[0037] (Preparation of the patch)
[0038] In the following examples, unless otherwise specified, the patches are prepared as follows.
[0039] 1) Mix the components of the adhesive layer and coat them onto the release film (a PET film that has undergone release treatment). Allow it to dry, and remove DMSO to the specified amount to form an adhesive layer with a thickness of 100 μm (100 g / m²). 2 ).
[0040] 2) Lay a support layer on the adhesive layer to obtain the patch. Cut the patch to the appropriate size.
[0041] (Measurement of the permeability of the supporting body layer)
[0042] In the following examples, the moisture permeability of the support layer used was measured according to JIS Z0208 under the conditions of 40°C and 90% RH.
[0043] (Evaluation of the adhesive properties of the patch)
[0044] In the following examples, unless otherwise specified, the adhesiveness of the patch is evaluated by the 180° peel test shown below.
[0045] 1) Prepare a 1cm×5cm test piece from the patch and store it under specified conditions for a specified time.
[0046] 2) Remove the release film from the test piece and attach the test piece to the stainless steel plate.
[0047] 3) Using an Instron tensile testing machine, tear the test piece from the stainless steel plate at a speed of 30 cm / min along a 180° direction and measure the peel force (gF / cm).
[0048] 4) Calculate the average peel force (gF / cm) from the cumulative value of the peel force in the region showing stable peeling. High peel force means excellent adhesion.
[0049] (Evaluation of patch adhesion)
[0050] In the following examples, the adhesion of the patch to the skin was evaluated using the method shown below. The patch was applied to the subject's skin. After 24 hours, the degree of adhesion was visually observed. A condition in which more than 90% of the patch area remained adhered to the skin was rated as "A", and other conditions were rated as "B".
[0051] (Experimental Example 1)
[0052] The patch (placebo patch) with the configuration shown in Table 1 was prepared. In the table, "PET film," "PET film / PET nonwoven fabric," "PU film / PU nonwoven fabric," and "PET woven fabric" refer to: a film containing PET, a laminate of a film containing PET and a nonwoven fabric containing PET fibers, a laminate of a film containing PU and a nonwoven fabric containing PU fibers, and a woven fabric containing PET, respectively. Furthermore, the rubber-based adhesive in Table 1 is a mixture of SIS block copolymer and PIB, containing SIS block copolymer and PIB in a mass ratio of 19:7. As for the "PET woven fabric," a moisture permeability of 5667 g / m² was used. 2• PET woven fabric with a 50% modulus of 3.9 N / 50 mm in the longitudinal direction and 3.4 N / 50 mm in the transverse direction (the same applies in the examples below) was used for 24 hours. The patch was placed with the support layer facing up and the release film facing down and stored in an incubator at 30°C and 65% RH. After 24 hours, DMSO was extracted from the patch and quantified by GC. These storage conditions simulate the environment when the patch is applied to the skin for 24 hours.
[0053] The results are shown in Table 1. Figure 1 and Figure 2 The moisture permeability of the support layer is 400 g / m². 2 • For reference examples 3 and 4, which last for more than 24 hours, the moisture permeability between the patch and the support layer is less than 400 g / m². 2 Compared to the patches in Reference Examples 1 and 2 after 24 hours, the DMSO concentration decreased significantly after storage. This indicates that for patches with a highly permeable support layer, the following relationship exists: the DMSO concentration in the adhesive layer decreases at a faster rate (…). Figure 1 ), DMSO concentration has a short half-life ( Figure 2 ).
[0054] In addition, the adhesiveness of the patch was evaluated after being stored under the same conditions for 24 hours. The results are shown in Table 1. The moisture permeability of the support layer was 400 g / m². 2 • For reference examples 3 and 4, which last for more than 24 hours, the moisture permeability between the patch and the support layer is less than 400 g / m². 2 • Compared to the patches in Reference Examples 1 and 2 after 24 hours, the adhesiveness (peel strength) was good after 24 hours of storage.
[0055] Furthermore, the adhesion of the patch constructed as shown in Table 1 was evaluated after 24 hours. The results are shown in Table 1. The moisture permeability of the support layer was 400 g / m². 2 • The patches in Reference Examples 3 and 4, applied for more than 24 hours, showed good adhesion after 24 hours.
[0056] [Table 1]
[0057]
[0058] (Experimental Example 2)
[0059] The patches shown in Table 2 were prepared. The rubber-based adhesive in Table 2 is a mixture of SIS block copolymer and PIB, containing SIS block copolymer and PIB in a mass ratio of 19:7. The adhesiveness of the patches in Examples 2, 7-9 was evaluated by the probe tack value measured according to the probe tack test method of ASTM D2979 under the following conditions. A high probe tack value indicates excellent adhesiveness.
[0060] Testing machine: Viscosity testing machine (Rhesca)
[0061] Probe tip material: Stainless steel
[0062] Diameter of the bonding surface: 5mm
[0063] Pull-off speed: 2mm / second
[0064] Adhesive load: 200 gF / cm 2
[0065] Bonding time: 1 second
[0066] In addition, one patch each of Examples 1-15 and Comparative Examples 1-3 were applied to the lower back of healthy adult males, and their adhesion was evaluated after 24 hours. The results are shown in Table 2. The moisture permeability of the support layer was 400 g / m². 2 • The patches of Examples 1 to 15 showed good adhesion after 24 hours of application.
[0067] Furthermore, the patch from Example 2 was stored in an incubator at 30°C and 65% RH with the support layer facing upwards. After 24 hours, the DMSO concentration (mass%) in the adhesive layer was quantified by GC to investigate the change in DMSO concentration. After 24 hours, the DMSO concentration relative to the total mass of the adhesive layer was 1.2% by mass, and its concentration relative to 100% of the initial (before storage) DMSO concentration was 33%. The rate of decrease in DMSO concentration, calculated from the change in DMSO concentration, was 0.1% by mass / hour, with a half-life of 15 hours.
[0068] [Table 2]
[0069]
[0070]
[0071] (Experimental Example 3)
[0072] The patches with the configuration shown in Table 3 were prepared. The probe tack value of the patches with the configuration shown in Table 3 was measured using the same method as in Example 2 to evaluate adhesion. The rubber-based adhesive in Table 3 is a mixture of SIS block copolymer and PIB, containing SIS block copolymer and PIB in a mass ratio of 19:7. "Rubber / Polyester Fabric" in Table 3 refers to polyester fabric coated with the rubber composition. The PU film (786 g / m² moisture permeability) in the patch of Example 16... 2 • 24 hours) and the PU film (8408 g / m²) in the patches of Examples 17, 19 and 20 2(24 hours) are 3M's "3MCoTran 9701Backing" and "3MCoTran 9700".
[0073] The adhesion of the patches from Examples 16-19 and Comparative Examples 4 and 5 was evaluated after 24 hours. The results are shown in Table 3. Furthermore, these patches from the examples and comparative examples were stored in an incubator at 30°C and 65% RH with the support layer facing upwards. After 24 hours, the DMSO concentration (mass%) in the adhesive layer was quantified by GC, and the change in DMSO concentration was investigated. The results are shown in Table 3. The moisture permeability of the support layer was 400 g / m². 2 • The patches of Examples 16-19 showed good adhesion after 24 hours of application.
[0074] [Table 3]
[0075]
Claims
1. A patch having a support layer and an adhesive layer laminated on the support layer, The moisture permeability of the support layer is 4000 g / m². 2 More than 24 hours The adhesive layer contains drugs, dimethyl sulfoxide, and rubber-based adhesives. The content of dimethyl sulfoxide is more than 1% by mass and less than 10% by mass relative to the total mass of the adhesive layer.
2. The patch according to claim 1, wherein, The adhesive layer contains a styrene-isoprene-styrene block copolymer.
3. The patch according to claim 1, wherein, The drug is selected from one or more drugs chosen from ketoprofen, diclofenac sodium, and indomethacin.
4. The patch according to claim 3, wherein, The adhesive layer contains organic acids.
Citation Information
Patent Citations
Skin patch
WO2013191128A1
Adhesive preparation
CN101442993A
Adhesive patch
CN101932329A
Patch material
CN102448449A
Patch and method for producing the same
CN103893156A